Antimicrobial photodynamic therapy – what we know and what we don't. (3rd September 2018) - Cieplik, Fabian; Deng, Dongmei; Crielaard, Wim; Buchalla, Wolfgang; Hellwig, Elmar; Al-Ahmad, Ali; Maisch, Tim
Abstract: Considering increasing number of pathogens resistant towards commonly used antibiotics as well as antiseptics, there is a pressing need for antimicrobial approaches that are capable of inactivating pathogens efficiently without the risk of inducing resistances. In this regard, an alternative approach is the antimicrobial photodynamic therapy (aPDT). The antimicrobial effect of aPDT is based on the principle that visible light activates a per se non-toxic molecule, the so-called photosensitizer (PS), resulting in generation of reactive oxygen species that kill bacteria unselectively via an oxidative burst. During the last 10–20 years, there has been extensive in vitro research on novel PS as well as light sources, which is now to be translated into clinics. In this review, we aim to provide an overview about the history of aPDT, its fundamental photochemical and photophysical mechanisms as well as photosensitizers and light sources that are currently applied for aPDT in vitro . Furthermore, the potential of resistances towards aPDT is extensively discussed and implications for proper comparison of in vitro studies regarding aPDT as well as for potential application fields in clinical practice are given. Overall, this review shall provide an outlook on future research directions needed for successful translation of promising in vitro results in aPDT towards clinical practice.